2020
DOI: 10.1021/acschemneuro.0c00644
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in Vitro Cannabinoid Receptor 1 Activity of Recently Detected Synthetic Cannabinoids 4F-MDMB-BICA, 5F-MPP-PICA, MMB-4en-PICA, CUMYL-CBMICA, ADB-BINACA, APP-BINACA, 4F-MDMB-BINACA, MDMB-4en-PINACA, A-CHMINACA, 5F-AB-P7AICA, 5F-MDMB-P7AICA, and 5F-AP7AICA

Abstract: Synthetic cannabinoid receptor agonists (SCRAs) are an evolving class of new psychoactive substances (NPS) with structurally diverse compounds emerging each year. Due to the rapid pace at which these drugs enter the market, there is often little or nil information regarding the pharmacology of these substances despite widespread human use. In this study, 12 recently emerged SCRAs (reported between 2018 and 2020) were synthesized, analytically characterized, and pharmacologically evaluated using a live cell-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
81
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 55 publications
15
81
0
Order By: Relevance
“…The EC 50 values for both reference compounds CP‐55,940 ( I ) (0.962 nM, 95% CI: 0.727–1.27) and JWH‐018 ( X ) (17.8 nM, 95% CI: 10.1–32.7) were in good agreement with previously reported data 3,13,14,19,29 . Very recently, Krotulski et al reported the pharmacological parameters for CB 1 for three of the tested substances, assessed using the same live cell‐based βarr2 recruitment assay, with results in good agreement with the present study: MMB‐4en‐PICA ( 1 ) (EC 50 : 125 nM, E max : 191% relative to 100% JWH‐018), MDMB‐4en‐PICA ( 2 ) (EC 50 : 11.5 nM, E max : 302% relative to 100% JWH‐018), and MDMB‐4en‐PINACA ( 12 ) (EC 50 : 2.47 nM, E max : 239% relative to 100% JWH‐018) 15,16 …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The EC 50 values for both reference compounds CP‐55,940 ( I ) (0.962 nM, 95% CI: 0.727–1.27) and JWH‐018 ( X ) (17.8 nM, 95% CI: 10.1–32.7) were in good agreement with previously reported data 3,13,14,19,29 . Very recently, Krotulski et al reported the pharmacological parameters for CB 1 for three of the tested substances, assessed using the same live cell‐based βarr2 recruitment assay, with results in good agreement with the present study: MMB‐4en‐PICA ( 1 ) (EC 50 : 125 nM, E max : 191% relative to 100% JWH‐018), MDMB‐4en‐PICA ( 2 ) (EC 50 : 11.5 nM, E max : 302% relative to 100% JWH‐018), and MDMB‐4en‐PINACA ( 12 ) (EC 50 : 2.47 nM, E max : 239% relative to 100% JWH‐018) 15,16 …”
Section: Resultssupporting
confidence: 92%
“…Following activation of CB 1 , βarr2 is recruited to the activated receptor, resulting in functional complementation of NanoLuc, which, in the presence of a suitable substrate, will result in luminescence. This assay has extensively been used for the functional characterization of a wide panel (>100) of SCRAs, in a multitude of publications 3,13–16 . The outcome of this functional evaluation was compared to existing structure activity data from literature.…”
Section: Introductionmentioning
confidence: 99%
“…), 110.5 (CH), 57.0 (CH), 52.3 (OCH 3 ), 46.2 (NCH 2 ), 31.9 (CH), 30.8 (CH 2 ), 29.0 (CH 2 ), 19.3 (CH 3 ), 18.2 (CH 3 ); v max 3331, 2962, 1739, 1629, 1508, 1466, 1388, 1279, 1229, 1175, 1146, 984, 911, 813, 780, 750, 636, 566, 541; HRMS (ESI+) C 20 H 26 N 2 O 3 [M + H] + exact mass 343.2022, accurate mass 343.2025 (mass error 2.49 ppm). All physical and spectral properties were consistent with previous reports 30 …”
Section: Methodssupporting
confidence: 92%
“…), 30.9 (CH 2 ), 28.9 (CH 2 ), 26.8 (CH 3 ); v max 3413, 2962, 1729, 1700, 1520, 1490, 1367, 1329, 1214, 1166, 988, 910, 833, 775, 755, 555; HRMS (ESI+) C 20 H 27 N 3 O 3 [M + H] + exact mass 358.2131, accurate mass 358.2134 (mass error 2.51 ppm). All physical and spectral properties were consistent with previous reports 30 …”
Section: Methodssupporting
confidence: 92%
“…As a limitation of our data, equivalent mouse pharmacokinetic data do not exist for 4-fluoro MDMB-BINACA and JWH 018 2′-naphthyl-N-(3-methylbutyl) and such data are beyond the scope of the present study. However, existing data presented here and elsewhere indicate that differences in SCRAs activity are pharmacodynamic rather than pharmacokinetic 45 47 . Although previous studies have not correlated the βarrestin2 bias of such ligands with specific in vivo effects, it is possible that βarrestin2-biased signaling may selectively enhance hypothermic and cataleptic responses relative to other cannabimimetic effects such as anti-nociception.…”
Section: Discussionmentioning
confidence: 60%